1. Wykonaj dzielenie.
a) (6x+24):3=
b) (8x-4y):4=
c) (4x+6:(-2)=
d) (-18x+6):(-6)=
e) ( -15a+25b) :(-5)=
f) (-x-y+7):(-1)=

2. Przekształć do najprostrzej postaci:

a) 7x-5(x-4)= 7x - 5x +20 (przykład)
b) -2y-3(-2y+1)=
c) -4(5z-1)-(4-9z)=
d) u+(6u-3):(-2)=

3. Oblicz wartość wyrażenia.
a) -6(-3x+1)-(4x+10):2 dla x= - 3/4
b) 10(2x+1/2-y)-(8x-6):(-2) dla x= -1/8 i y=2

FAST DAJE 50pkt... ;)

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-22T17:03:09+01:00
1. Wykonaj dzielenie.
a) (6x+24):3= 6(x+4) / 3 = 2(x+4) = 2x+8
b) (8x-4y):4= 4(2x-y)/4 = 2x-y
c) (4x+6:(-2)= 2(2x+3)/(-2) = -(2x+3) = -2x-3
d) (-18x+6):(-6)= -6(3x-1)/(-6) = 3x-1
e) ( -15a+25b) :(-5)= -5(3a-5b)/(-5) = 3a-5b
f) (-x-y+7):(-1)= x+y-7

2. Przekształć do najprostszej postaci:

a) 7x-5(x-4)= 7x - 5x +20 (przykład)
b) -2y-3(-2y+1)= -2y+6y-3 = 4y-3
c) -4(5z-1)-(4-9z)= -20z+4-4+9z = -11z
d) u+(6u-3):(-2)= u+ (2(3u-3/2))/(-2) = u-3u+3/2 = -2u+3/2

3. Oblicz wartość wyrażenia.
a) -6(-3x+1)-(4x+10):2 dla x= - 3/4
18x-6- (2(2x+5))/2 = 18x-6-2x-5=16x-11 = 16*(-3/4)-11 = -12-11 = -33

b) 10(2x+1/2-y)-(8x-6):(-2) dla x= -1/8 i y=2
20x+5-10y- (2(4x-3))/(-2) = 20x+5-10y+4x-3 = 24x-10y+2 = 24*(-1/8)-10*2+2 = -3-20+2 = -23+2 = -21

2010-03-22T17:15:23+01:00

1.-a) (6x+24):3= 6(x+4) / 3 = 2(x+4) = 2x+8
- (8x-4y):4= 4(2x-y)/4 = 2x-y
- (4x+6:(-2)= 2(2x+3)/(-2) = -(2x+3) = -2x-3
- (-18x+6):(-6)= -6(3x-1)/(-6) = 3x-1
- ( -15a+25b) :(-5)= -5(3a-5b)/(-5) = 3a-5b
- (-x-y+7):(-1)= x+y-7



2.- 7x-5(x-4)= 7x - 5x +20
- -2y-3(-2y+1)= -2y+6y-3 = 4y-3
- -4(5z-1)-(4-9z)= -20z+4-4+9z = -11z
- u+(6u-3):(-2)= u+ (2(3u-3/2))/(-2) = u-3u+3/2 = -2u+3/2


3. -6(-3x+1)-(4x+10):2 dla x= - 3/4
18x-6- (2(2x+5))/2 = 18x-6-2x-5=16x-11 = 16*(-3/4)-11 = -12-11 = -33

b) 10(2x+1/2-y)-(8x-6):(-2) dla x= -1/8 i y=2
20x+5-10y- (2(4x-3))/(-2) = 20x+5-10y+4x-3 = 24x-10y+2 = 24*(-1/8)-10*2+2 = -3-20+2 = -23+2 = -21